EU Eastern Neighborhood 2011
DOI: 10.1007/978-3-642-21093-8_1
|View full text |Cite
|
Sign up to set email alerts
|

The Development Gap Between the CIS and EU

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A study by Sinitsina et al. () on development gaps between the Commonwealth of Independent States and the EU revealed that the speed and depth of market reforms are important: a split of the sample into ‘active reformers’ and ‘slow and partial reformers’ slowed a clear positive relationship between reform progress and convergence.…”
Section: The Theory Underpinning Economic Convergencementioning
confidence: 99%
“…A study by Sinitsina et al. () on development gaps between the Commonwealth of Independent States and the EU revealed that the speed and depth of market reforms are important: a split of the sample into ‘active reformers’ and ‘slow and partial reformers’ slowed a clear positive relationship between reform progress and convergence.…”
Section: The Theory Underpinning Economic Convergencementioning
confidence: 99%